bc3286
contestada

Ariana correctly simplify an expression. When she substituted x equals 2 into the simplify expression, the value was -4 which could be Ariana's original expression

1/6(-3x-24)

1/6(-5x-8)

1/6(-10x-4)

1/6(-12x-16)

Ariana correctly simplify an expression When she substituted x equals 2 into the simplify expression the value was 4 which could be Arianas original expression1 class=

Respuesta :

The correct answer would be C. Hope it helps :)

Answer:

Ariana's original expression  is

[tex]\dfrac{1}{6}\times (-10x-4)[/tex]

Step-by-step explanation:

  • [tex]\dfrac{1}{6}\times (-3x-24)\\\\at\ x=2,\ we\ get\\\\\dfrac{1}{6}\times (-30)\\ \\=-5[/tex]
  • [tex]\dfrac{1}{6}\times (-5x-8)\\\\at\ x=2,\ we\ get\\\\\dfrac{1}{6}\times (-18)\\ \\=-3[/tex]
  • [tex]\dfrac{1}{6}\times (-10x-4)\\\\at\ x=2,\ we\ get\\\\\dfrac{1}{6}\times (-24)\\ \\=-4[/tex]
  • [tex]\dfrac{1}{6}\times (-12x-16)\\\\at\ x=2,\ we\ get\\\\\dfrac{1}{6}\times (-40)\\ \\=-20/3[/tex]

Hence, Ariana's original expression  is

[tex]\dfrac{1}{6}\times (-10x-4)[/tex]